Flavoured leptogenesis and CPμτ symmetry - Rome Samanta; Manibrata Sen (Journal of High Energy Physics)
Abstract We present a systematic study of leptogenesis in neutrino mass models with μτ-flavoured CP symmetry. In addition to the strong hierarchical N1-dominated scenario (N1DS) in the ‘two flavour regime’ of leptogenesis, we show that one may choose the right-handed (RH) neutrino mass hierarchy as mild as M2 ≃ 4.7M1 for a perfectly valid hierarchical N1DS. This reduces the lower bound on the allowed values of M1, compared to what is stated in the literature. The consideration of flavour effects due to the heavy neutrinos also translate into an upper bound on M1. It is only below this bound that the observed baryon-to-photon ratio can be realized for a standard N1 domination, else a substantial part of the parameter space is also compatible with N2DS. We deduce conditions under which the baryon asymmetry produced by the second RH neutrino plays an important role. Finally, we discuss another scenario where lepton asymmetry generated by N2 in the two flavour regime faces washout by N1 in the three flavour regime. Considering a hierarchical light neutrino mass spectrum, which is now favoured by cosmological observations, we show that at the end of N1-leptogenesis, the asymmetry generated by N2 survives only in the electron flavour and about 33% of the parameter space is consistent with a pure N2-leptogenesis.